Orthostatic Heart Rate Changes in Patients with Autonomic Failure caused by Neurodegenerative Synucleinopathies - Norcliffe-Kaufmann, Lucy (Ann Neurol, 2018)
OBJECTIVE: Blunted tachycardia during hypotension is a characteristic feature of patients with autonomic failure, but the range has not been defined. This study reports the range of orthostatic heart rate (HR) changes in patients with autonomic failure caused by neurodegenerative synucleinopathies. METHODS: Patients evaluated at sites of the U.S. Autonomic Consortium (NCT01799915) underwent standardized autonomic function tests and full neurological evaluation. RESULTS: We identified 402 patients with orthostatic hypotension (OH) who had normal sinus rhythm. Of these, 378 had impaired sympathetic activation, i.e., neurogenic OH, and based on their neurological examination were diagnosed with Parkinson disease, dementia with Lewy bodies, pure autonomic failure or multiple system atrophy. The remaining 24 patients had preserved sympathetic activation and their OH was classified as non-neurogenic, due to volume depletion, anemia or polypharmacy. Patients with neurogenic OH had twice the fall in systolic blood pressure (SBP) [−44±25 vs. −21±14 mmHg (mean±SD), p<0.0001] but only one third of the increase in HR than those with non-neurogenic OH (8±8 vs. 25±11 bpm, p<0.0001). A ΔHR/ΔSBP ratio of 0.492 bpm/mmHg had excellent sensitivity (91.3%) and specificity (88.4%) to distinguish between patients with neurogenic vs. non-neurogenic OH (AUC=0.96, p<0.0001). Within patients with neurogenic OH, HR increased more in those with multiple system atrophy (p=0.0003), but there was considerable overlap with patients with Lewy body disorders. INTERPRETATION: A blunted HR increase during hypotension suggests a neurogenic cause. A ΔHR/ΔSBP ratio lower than 0.5 bpm/mmHg is diagnostic of neurogenic OH.